Region and layer-specific expression of GABAA receptor isoforms and KCC2 in developing cortex - Zavalin, Kirill; Hassan, Anjana; Zhang, Yueli; Khera, Zain; Lagrange, Andre H. (Frontiers in Cellular Neuroscience, 2024)
γ-Aminobutyric acid (GABA) type A receptors (GABA A Rs) are ligand-gated Cl -channels that mediate the bulk of inhibitory neurotransmission in the mature CNS and are targets of many drugs. During cortical development, GABA A R-mediated signals are significantly modulated by changing subunit composition and expression of Cl -transporters as part of developmental processes and early network activity. To date, this developmental evolution has remained understudied, particularly at the level of cortical layer-specific changes. In this study, we characterized the expression of nine major GABA A R subunits and K-Cl transporter 2 (KCC2) in mouse somatosensory cortex from embryonic development to postweaning maturity. Similarly to previous studies, we found that embryonic cortex expresses mainly ɑ3, ɑ5, β3, and γ2, while expression of ɑ1, ɑ2, ɑ4, β2, δ, and KCC2 begins at later points in development. However, we also found unique patterns of temporal, regional, and laminar expression of each subunit and KCC2 that were previously unknown.